Budgeting: planning for success - budgeting and decision making - Walther, Larry M.; Skousen, Christopher J. (Bookboon, 2010)
This book is the twelfth of fifteen books which introduces the basic principles of accounting. In this book you will learn about using budgeting to plan for success. The importance of budgeting is emphasized, while focusing on the process and human behavior. Various forms of budgets are introduced. The major managerial budgets are presented, including: sales, production, direct materials purchases, direct labor, factory overhead, selling and administrative expense, and cash. Budget financial statements are also discussed.
Printed from the Bookboon website
oif 27/02/17
Loans
Keywords: Budgets